Fostering Critical Collaborative Thinking through Digital Platform: An Empirical Study on Interdisciplinary Design Project - Aswin Indraprastha (Department of Architecture Universitas Muhammadiyah Jakarta, 2023)
This study addressed an increasing need for collaborative skills for architecture graduates in the AEC (Architecture, Engineering, and Construction) industries and fill in the gap of studies in collaborative engagements in architecture schools where most of the studies had focused on the creative collaboration in the design process to increase collaborative teamwork within architecture students. The study was conducted as a project-based interdisciplinary course for 4th-year undergraduate programs which involves engineering departments: Civil and Environmental Engineering, Mechanical Engineering, Electrical Engineering, Engineering Physics, and Interior Design. The aim of the study is to critically evaluate the experience gained in the collaborative and interdisciplinary courses, as well as a valuable lesson learned based on students' perspectives. The results showed that an innovative pedagogy must be provided to foster collaborative works, through a concurrent-integrative approach. Another finding is the digital platform potentially increases students’ engagement in interactive discussion and teamwork when appropriately implemented. This was confronted with several challenges, specifically the legacy of a conventional mono-discipline pedagogy and the liberation of critical collaborative thinking among the students.